The Effect of Pornography Exposure in Social Media to Premarital Sexual Behaviour Towards Teenagers at SMA Negeri 1 Central Kupang - Dimu, Yohana; Adu, Apris A; Riwu, Rut Rosina (Universitas Nusa Cendana, 2023)
Premarital sexual behavior is sexual behavior that is carried out without going through an official marriage process according to the law or religion and beliefs of each. Based on the initial survey results, college students have had premarital sex up to the stage of kissing, touching sensitive parts/areas, and petting to the point of pregnancy. This research determines the effect of exposure to pornography on social media on premarital sex behavior in adolescents at SMA Negeri 1 Central Kupang. This research is an analytical study, and the design approach is cross-sectional. The sample size was 186 students in classes X and XI. The sampling technique is the probability sampling technique, with the type used being proportionate stratified random sampling. The results showed that from 186 respondents, 139 people had been exposed to pornography on social media, and from 139 respondents who were exposed to pornography, 89 people had light sex, and 50 had heavy sex. The results of the statistical analysis test showed that there was a significant effect between exposure to pornography on social media and premarital sexual behavior in adolescents at SMA Negeri 1 Kupang Tengah, with a p-value of 0.001 (p <0.05). Based on the results of the study, it is hoped that schools and parents can provide education to teenagers to be more selective in using social media and provide sex education as early as possible so that they can know about sex and the impact of having sex at an early age so that teenagers can limit themselves more in behavior, especially premarital sex behavior.